Environmental politics and policy in the west - Freemuth, John C. (John Carter); Smith, Zachary A. (Zachary Alden), 1953- (University Press of Colorado, 2016)
"This new edition offers a comprehensive and current survey of major western policy and environmental issues. Contributors address the policy process as it affects the states in the region, and how bureaucracy and politics shape environmental dialogues in the West."--